Implementasi Kegiatan Bercocok Tanam dalam Pembelajaran Sains Anak Usia 4-6 Tahun (Penelitian Kualitatif Deskriptif di TK Kemala Bhayangkari 05 Serang Banten) - Alfia Batshila; Siti Khosiah; Tri Sayekti (Darul Yasin Al Sys, 2026)
Science learning in early childhood often remains abstract and provides limited direct experience, so children’s involvement in the learning process has not yet been optimal. Therefore, contextual and real experience-based learning activities are needed, one of which is planting activities. This study aims to describe the implementation of planting activities in science learning for children aged 4–6 years at TK Kemala Bhayangkari 05 Serang, Banten. This study employed a qualitative approach with a descriptive method. The research subjects consisted of teachers, the principal, and children aged 4–6 years. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing, with data validity tested using source and technique triangulation. The results showed that the implementation of planting activities was carried out through three main stages, namely planning, implementation, and learning evaluation. This activity was able to increase children’s active involvement in science learning and develop science process skills, such as observing, asking questions, and communicating observation results. Children were also able to understand the concepts of plant growth and the needs of living things more concretely. In addition, planting activities fostered environmental awareness and responsibility in children. Thus, planting activities can become an effective, contextual, and meaningful science learning strategy for early childhood. The implications of this study indicate that science learning based on direct experience can improve the quality of learning and encourage teachers to develop more creative and environment-based learning activities.